Facing somatic symptom disorder in the emergency department. - Cozzi, Giorgio; Barbi, Egidio (J Paediatr Child Health, 2019)
Somatic symptom disorder is a condition in which a patient's subjective report of physical symptoms is associated with distress; disruption of day-to-day functioning; or disproportionate thoughts, feelings and behaviours regarding the symptoms, whether or not they are associated with an identified medical condition. While somatic symptom disorder affects a considerable proportion of children and adolescents presenting to the emergency department (ED), it has not been well investigated in the ED literature, nor is there much formal training in, or guidelines for, how to care for affected patients in the ED. The aim of this paper is to highlight the historical clues commonly reported by these patients in order to try to help the emergency physicians recognise patients affected by a somatic symptom disorder. Adolescent age, the presence of daily subjective symptoms presenting daily for weeks or months, a long medical history record, an extensive diagnostic workup and, most of all, disproportionate functional impairment related to the symptoms are all features strongly suggestive of this disorder. Emergency physicians should become used to taking advantage of these clues to formulate a positive diagnosis of somatic symptom disorder according to the most recent diagnostic criteria. Emergency physicians have the unique opportunity to contribute to the correct diagnosis and treatment of these patients and to have a positive impact on their prognosis.

First urinary tract infections in children: the role of the risk factors proposed by the Italian recommendations. - Alberici, I; La Manna, A; Pennesi, M; Starc, M; Scozzola, F; Nicolini, G; Toffolo, A; Marra, G; Chimenz, R; Sica, F; Maringhini, S; Monasta, L; et al. (Acta Paediatr, 2019)
AIM: In 2009, the Italian society for paediatric nephrology suggested the need for cystography, following a first febrile urinary tract infection (UTI), only in children at high risk for dilating vesicoureteral reflux or in the event of a second infection. The aim of this study was to evaluate the adequacy of the risk factors proposed by the Italian guidelines. METHODS: Children aged 2-36 months, managed by 10 Italian hospitals between 2009 and 2013, with a first febrile UTI were retrospectively evaluated. RESULTS: Four hundred and fourteen children were included: 51% female, mean age eight months. Escherichia coli was responsible of 84% UTIs. 269 children (65%) presented at least one risk factor, thus were further investigated: 44% had a reflux. The presence of a pathogen other than E. coli significantly predicted high-grade reflux, both in the univariate (Odd Ratio 2.52, 95% Confidence Interval 1.32-4.81, p < 0.005) and multivariate analysis (OR 2.74, 95% CI: 1.39-5.41, p: 0.003). 26/145 children (18%) with no risk factors experienced a second UTI, which prompted the execution of cystography, showing a dilating reflux in 11. CONCLUSION: Among the risk factors proposed by the Italian guidelines, only the presence of a pathogen other than E. coli significantly predicted reflux. Cystography can be postponed in children with no risk factors.

Four-miRNA Signature to Identify Asbestos-Related Lung Malignancies. - Santarelli, Lory; Gaetani, Simona; Monaco, Federica; Bracci, Massimo; Valentino, Matteo; Amati, Monica; Rubini, Corrado; Sabbatini, Armando; Pasquini, Ernesto; Zanotta, Nunzia; Comar, Manola; Neuzil, Jiri; et al. (Cancer Epidemiol Biomarkers Prev, 2019)
BACKGROUND: Altered miRNA expression is an early event upon exposure to occupational/environmental carcinogens; thus, identification of a novel asbestos-related profile of miRNAs able to distinguish asbestos-induced cancer from cancer with different etiology can be useful for diagnosis. We therefore performed a study to identify miRNAs associated with asbestos-induced malignancies. METHODS: Four groups of patients were included in the study, including patients with asbestos-related (NSCLC) and asbestos-unrelated non-small cell lung cancer (NSCLC) or with malignant pleural mesothelioma (MPM), and disease-free subjects (CTRL). The selected miRNAs were evaluated in asbestos-exposed population. RESULTS: Four serum miRNAs, that is miR-126, miR-205, miR-222, and miR-520g, were found to be implicated in asbestos-related malignant diseases. Notably, increased expression of miR-126 and miR-222 were found in asbestos-exposed subjects, and both miRNAs are involved in major pathways linked to cancer development. Epigenetic changes and cancer-stroma cross-talk could induce repression of miR-126 to facilitate tumor formation, angiogenesis, and invasion. CONCLUSIONS: This study indicates that miRNAs are potentially involved in asbestos-related malignancies, and their expression outlines mechanism(s) whereby miRNAs may be involved in an asbestos-induced pathogenesis. IMPACT: The discovery of a miRNA panel for asbestos-related malignancies would impact on occupational compensation and may be utilized for screening asbestos-exposed populations.

Facilitators and barriers to the effective implementation of the individual maternal near-miss case reviews in low/middle-income countries: a systematic review of qualitative studies. - Lazzerini, Marzia; Ciuch, Margherita; Rusconi, Silvia; Covi, Benedetta (BMJ Open, 2018)
BACKGROUND: The maternal near-miss cases review (NMCR), a type of clinical audit, proved to be effective in improving quality of care and decreasing maternal mortality in low/middle-income countries (LMICs). However, challenges in its implementation have been described. OBJECTIVES: Synthesising the evidence on facilitators and barriers to the effective implementation of NMCR in LMICs. DESIGN: Systematic review of qualitative studies. DATA SOURCES: MEDLINE, LILACS, Global Health Library, SCI-EXPANDED, SSCI, Cochrane library and Embase were searched in December 2017. ELIGIBILITY CRITERIA FOR SELECTING STUDIES: Qualitative studies exploring facilitators and/or barriers of implementing NMCR in LMIC were included. DATA EXTRACTION AND SYNTHESIS: Two independent reviewers extracted data, performed thematic analysis and assessed risk of bias. RESULTS: Out of 25 361 papers retrieved, 9 studies from Benin, Brazil, Burkina Faso, Cote D'Ivoire, Ghana, Malawi, Morocco, Tanzania, Uganda could be included in the review. The most frequently reported barriers to NMCR implementation were the following: absence of national guidelines and local protocols; insufficient training on how to perform the audit; lack of leadership, coordination, monitoring and supervision; lack of resources and work overload; fear of blame and punishment; poor knowledge of evidenced-based medicine; hierarchical differences among staff and poor understating of the benefits of the NMCR. Major facilitators to NMCR implementation included: good leadership and coordination; training of all key staff; a good cultural environment; clear staff's perception on the benefits of conducting audit; patient empowerment and the availability of external support. CONCLUSIONS: In planning the NMCR implementation in LMICs, policy-makers should consider actions to prevent and mitigate common challenges to successful NMCR implementation. Future studies should aim at documenting facilitators and barriers to NMCR outside the African Region.

Fecal Calprotectin to Detect Inflammatory Bowel Disease in Juvenile Idiopathic Arthritis. - Ferrara, Giovanna; Pastore, Serena; Sancin, Lara; Torelli, Lucio; Radillo, Oriano; Bramuzzo, Matteo; Bibalo, Chiara; Tommasini, Alberto; Ventura, Alessandro; Taddio, Andrea (J Rheumatol, 2018)
OBJECTIVE: This study aimed to test fecal calprotectin (FC) as a screening tool to identify inflammatory bowel disease (IBD) among patients with juvenile idiopathic arthritis (JIA). METHODS: FC level < 100 g/kg was considered normal. Patients with 2 consecutive FC dosage ≥ 100 g/kg underwent endoscopic evaluation. RESULTS: There were 113 patients with JIA enrolled. FC was raised in 7 patients out of 113. All patients had IBD. In 3/7 patients, high FC levels were the only sign consistent with IBD. CONCLUSION: FC is a useful, economical, and noninvasive diagnostic tool to identify JIA patients with underlying IBD.

Ferruginous bodies resolved by synchrotron XRF in a dog with peritoneal malignant mesothelioma. - Pascotto, Ernesto; Gianoncelli, Alessandra; Calligaro, Carla; Marcuzzo, Thomas; Melato, Mauro; Rizzardi, Clara; Pascolo, Lorella (Environ Sci Pollut Res Int, 2018)
Mesothelioma is a malignant tumor mainly correlated to occupational asbestos exposure. Rare reports describe its occurrence also in animals, mainly linked to asbestos in the environment. Asbestos exposure is demonstrated by the appearance of characteristic histological hallmarks: asbestos containing ferruginous bodies that are iron-based structures forming around fibers and also other dust particles. Here we present a clinical case of a suspect of mesothelioma in the peritoneum of a dog with parallel histological observation of ferruginous bodies. To possibly correlate the dog tumor to environmental exposure, we performed X-ray fluorescence (XRF) analyses at two different synchrotrons to resolve the ferruginous bodies' composition. While the histological examination diagnoses a tubulo-papillary mesothelioma, the XRF analyses show that ferruginous bodies contain Si particles, resembling formations of exogenous origin; however, the morphology is unlikely that of asbestos fibers. We speculate that the peritoneal mesothelioma of this dog could be related to environmental exposure to non-asbestos material.
Keywords: Animals; Asbestos; Dogs; Environmental Exposure; Immunohistochemistry; Iron; Lung; Lung Neoplasms; Male; Mesothelioma; Peritoneal Neoplasms; Silicon; Spectrometry, X-Ray Emission; Synchrotrons

Flares After Withdrawal of Biologic Therapies in Juvenile Idiopathic Arthritis: Clinical and Laboratory Correlates of Remission Duration. - Simonini, Gabriele; Ferrara, Giovanna; Pontikaki, Irene; Scoccimarro, Erika; Giani, Teresa; Taddio, Andrea; Meroni, Pier Luigi; Cimaz, Rolando (Arthritis Care Res (Hoboken), 2018)
OBJECTIVE: To assess the time in remission after discontinuing biologic therapy in patients with juvenile idiopathic arthritis (JIA). METHODS: We enrolled 135 patients followed in 3 tertiary-care centers. The primary outcome was to assess, once remission was achieved, the time in remission up to the first flare after discontinuing treatment. Mann-Whitney U test, Wilcoxon's signed rank test for paired samples, chi-square tests, and Fisher's exact test were used to compare data. Pearson's and Spearman's correlation tests were used to determine correlation coefficients for different variables. To identify predictors of outcome, Cox regression model and Kaplan-Meier curves were constructed, each one at the mean of entered covariates. RESULTS: The majority of enrolled patients flared after stopping treatment with biologics (102 of 135, 75.6%) after a median followup time in remission off therapy of 6 months (range 3-109 months). A higher probability of maintaining remission after discontinuing treatment was present in systemic-onset disease compared to the rest of the JIA patients (Mantel-Cox χ = 8.31, P < 0.004). In analysis limited to children with JIA with polyarticular and oligoarticular disease, patients who received biologics >2 years after achieving remission had a higher probability of maintaining such remission off therapy (mean ± SD 18.64 ± 3.3 months versus 11.51 ± 2.7 months [P < 0.009]; Mantel-Cox χ = 9.06, P < 0.002). No other clinical variable was significantly associated with a long-lasting remission. CONCLUSION: Children with oligoarticular and polyarticular JIA who stop treatment before 2 years from remission have a higher chance of relapsing after biologic withdrawal.

Fractional CO laser for genitourinary syndrome of menopause in breast cancer survivors: clinical, immunological, and microbiological aspects. - Becorpi, Angelamaria; Campisciano, Giuseppina; Zanotta, Nunzia; Tredici, Zelinda; Guaschino, Secondo; Petraglia, Felice; Pieralli, Annalisa; Sisti, Giovanni; De Seta, Francesco; Comar, Manola (Lasers Med Sci, 2018)
The composition of vaginal microbiome in menopause and cancer survivor women changes dramatically leading to genitourinary syndrome of menopause (GSM) in up to 70% of patients. Recent reports suggest that laser therapy may be valuable as a not hormonal therapeutic modality. The aim of the present study was to evaluate the effects of fractional CO laser treatment on the vaginal secretory pathway of a large panel of immune mediators, usually implicated in tissue remodeling and inflammation, and on microbiome composition in postmenopausal breast cancer survivors. The Ion Torrent PGM platform and the Luminex Bio-Plex platform were used for microbiome and immune factor analysis. The significant reduction of clinical symptoms and the non-significant changes in vaginal microbiome support the efficacy and safety of laser treatment. Moreover, the high remodeling status in vaginal epithelium is demonstrated by the significant changes in inflammatory and modulatory cytokine patterns. Laser therapy can be used for the treatment of GSM symptoms and does not show any adverse effects. However, further studies will be needed to clarify its long-term efficacy and other effects.
Keywords: Breast Neoplasms; Cancer Survivors; Cytokines; Dyspareunia; Female; Humans; Lasers, Gas; Menopause; Microbiota; Middle Aged; Prospective Studies; Syndrome; Vagina; Vaginal Diseases

Factors Influencing the Phenotypic Characterization of the Oral Marker, PROP. - Tepper, Beverly J; Melis, Melania; Koelliker, Yvonne; Gasparini, Paolo; Ahijevych, Karen L; Tomassini Barbarossa, Iole (Nutrients, 2017)
In the last several decades, the genetic ability to taste the bitter compound, 6--propyltiouracil (PROP) has attracted considerable attention as a model for understanding individual differences in taste perception, and as an oral marker for food preferences and eating behavior that ultimately impacts nutritional status and health. However, some studies do not support this role. This review describes common factors that can influence the characterization of this phenotype including: (1) changes in taste sensitivity with increasing age; (2) gender differences in taste perception; and (3) effects of smoking and obesity. We suggest that attention to these factors during PROP screening could strengthen the associations between this phenotype and a variety of health outcomes ranging from variation in body composition to oral health and cancer risk.
Keywords: Food Preferences; Genetic Variation; Humans; Propylthiouracil; Taste Perception; Taste Threshold

Fetal and umbilical Doppler ultrasound in high-risk pregnancies. - Alfirevic, Zarko; Stampalija, Tamara; Dowswell, Therese (Cochrane Database Syst Rev, 2017)
BACKGROUND: Abnormal blood flow patterns in fetal circulation detected by Doppler ultrasound may indicate poor fetal prognosis. It is also possible that false positive Doppler ultrasound findings could lead to adverse outcomes from unnecessary interventions, including preterm delivery. OBJECTIVES: The objective of this review was to assess the effects of Doppler ultrasound used to assess fetal well-being in high-risk pregnancies on obstetric care and fetal outcomes. SEARCH METHODS: We updated the search of Cochrane Pregnancy and Childbirth's Trials Register on 31 March 2017 and checked reference lists of retrieved studies. SELECTION CRITERIA: Randomised and quasi-randomised controlled trials of Doppler ultrasound for the investigation of umbilical and fetal vessels waveforms in high-risk pregnancies compared with no Doppler ultrasound. Cluster-randomised trials were eligible for inclusion but none were identified. DATA COLLECTION AND ANALYSIS: Two review authors independently assessed the studies for inclusion, assessed risk of bias and carried out data extraction. Data entry was checked. We assessed the quality of evidence using the GRADE approach. MAIN RESULTS: Nineteen trials involving 10,667 women were included. Risk of bias in trials was difficult to assess accurately due to incomplete reporting. None of the evidence relating to our main outcomes was graded as high quality. The quality of evidence was downgraded due to missing information on trial methods, imprecision in risk estimates and heterogeneity. Eighteen of these studies compared the use of Doppler ultrasound of the umbilical artery of the unborn baby with no Doppler or with cardiotocography (CTG). One more recent trial compared Doppler examination of other fetal blood vessels (ductus venosus) with computerised CTG.The use of Doppler ultrasound of the umbilical artery in high-risk pregnancy was associated with fewer perinatal deaths (risk ratio (RR) 0.71, 95% confidence interval (CI) 0.52 to 0.98, 16 studies, 10,225 babies, 1.2% versus 1.7 %, number needed to treat (NNT) = 203; 95% CI 103 to 4352, evidence graded moderate). The results for stillbirths were consistent with the overall rate of perinatal deaths, although there was no clear difference between groups for this outcome (RR 0.65, 95% CI 0.41 to 1.04; 15 studies, 9560 babies, evidence graded low). Where Doppler ultrasound was used, there were fewer inductions of labour (average RR 0.89, 95% CI 0.80 to 0.99, 10 studies, 5633 women, random-effects, evidence graded moderate) and fewer caesarean sections (RR 0.90, 95% CI 0.84 to 0.97, 14 studies, 7918 women, evidence graded moderate). There was no comparative long-term follow-up of babies exposed to Doppler ultrasound in pregnancy in women at increased risk of complications.No difference was found in operative vaginal births (RR 0.95, 95% CI 0.80 to 1.14, four studies, 2813 women), nor in Apgar scores less than seven at five minutes (RR 0.92, 95% CI 0.69 to 1.24, seven studies, 6321 babies, evidence graded low). Data for serious neonatal morbidity were not pooled due to high heterogeneity between the three studies that reported it (1098 babies) (evidence graded very low).The use of Doppler to evaluate early and late changes in ductus venosus in early fetal growth restriction was not associated with significant differences in any perinatal death after randomisation. However, there was an improvement in long-term neurological outcome in the cohort of babies in whom the trigger for delivery was either late changes in ductus venosus or abnormalities seen on computerised CTG. AUTHORS' CONCLUSIONS: Current evidence suggests that the use of Doppler ultrasound on the umbilical artery in high-risk pregnancies reduces the risk of perinatal deaths and may result in fewer obstetric interventions. The results should be interpreted with caution, as the evidence is not of high quality. Serial monitoring of Doppler changes in ductus venosus may be beneficial, but more studies of high quality with follow-up including neurological development are needed for evidence to be conclusive.
Keywords: Cardiotocography; Cesarean Section; Female; Fetal Monitoring; Humans; Labor, Induced; Perinatal Mortality; Pregnancy; Pregnancy, High-Risk; Randomized Controlled Trials as Topic; Stillbirth; Ultrasonography, Prenatal; Umbilical Arteries; Umbilical Cord

Fetal monitoring indications for delivery and 2-year outcome in 310 infants with fetal growth restriction delivered before 32 weeks' gestation in the TRUFFLE study. - Visser, G H A; Bilardo, C M; Derks, J B; Ferrazzi, E; Fratelli, N; Frusca, T; Ganzevoort, W; Lees, C C; Napolitano, R; Todros, T; Wolf, H; Hecher, K (Ultrasound Obstet Gynecol, 2017)
OBJECTIVE: In the TRUFFLE (Trial of Randomized Umbilical and Fetal Flow in Europe) study on the outcome of early fetal growth restriction, women were allocated to one of three groups of indication for delivery according to the following monitoring strategies: (1) reduced fetal heart rate (FHR) short-term variation (STV) on cardiotocography (CTG); (2) early changes in fetal ductus venosus (DV) waveform (DV-p95); and (3) late changes in fetal DV waveform (DV-no-A). However, many infants per monitoring protocol were delivered because of safety-net criteria, for maternal or other fetal indications, or after 32 weeks of gestation when the protocol was no longer applied. The objective of the present posthoc subanalysis was to investigate the indications for delivery in relation to 2-year outcome in infants delivered before 32 weeks to further refine management proposals. METHODS: We included all 310 cases of the TRUFFLE study with known outcome at 2 years' corrected age and seven fetal deaths, excluding seven cases with inevitable perinatal death. Data were analyzed according to the allocated fetal monitoring strategy in combination with the indication for delivery. RESULTS: Overall, only 32% of liveborn infants were delivered according to the specified monitoring parameter for indication for delivery; 38% were delivered because of safety-net criteria, 15% for other fetal reasons and 15% for maternal reasons. In the CTG-STV group, 51% of infants were delivered because of reduced STV. In the DV-p95 group, 34% of infants were delivered because of abnormal DV and, in the DV-no-A group, only 10% of infants were delivered accordingly. The majority of infants in the DV groups were delivered for the safety-net criterion of spontaneous decelerations in FHR. Two-year intact survival was highest in the DV groups combined compared with the CTG-STV group (P = 0.05 for live births only, P = 0.21 including fetal death), with no difference between DV groups. A poorer outcome in the CTG-STV group was restricted to infants delivered because of FHR decelerations in the safety-net subgroup. Infants delivered because of maternal reasons had the highest birth weight and a non-significantly higher intact survival. CONCLUSIONS: In this subanalysis of infants delivered before 32 weeks, the majority were delivered for reasons other than the allocated monitoring strategy indication. Since, in the DV group, CTG-STV criteria were used as a safety net but in the CTG-STV group, no DV safety-net criteria were applied, we speculate that the slightly poorer outcome in the CTG-STV group might be explained by the absence of DV data. The optimal timing of delivery of fetuses with early intrauterine growth restriction may therefore be best determined by monitoring them longitudinally, with both DV and CTG monitoring. Copyright © 2016 ISUOG. Published by John Wiley & Sons Ltd.
Keywords: Cardiotocography; Delivery, Obstetric; Female; Fetal Growth Retardation; Fetal Monitoring; Fetus; Gestational Age; Humans; Infant, Newborn; Male; Netherlands; Pregnancy; Pregnancy Outcome; Pulsatile Flow; Survival Analysis; Ultrasonography, Prenatal; Umbilical Arteries

First-time success with needle procedures was higher with a warm lidocaine and tetracaine patch than an eutectic mixture of lidocaine and prilocaine cream. - Cozzi, Giorgio; Borrometi, Fabio; Benini, Franca; Neri, Elena; Rusalen, Francesca; Celentano, Loredana; Zanon, Davide; Schreiber, Silvana; Ronfani, Luca; Barbi, Egidio (Acta Paediatr, 2017)
AIM: More than 50% of children report apian during venepuncture or intravenous cannulation and using local anaesthetics before needle procedures can lead to different success rates. This study examined how many needle procedures were successful at the first attempt when children received either a warm lidocaine and tetracaine patch or an eutectic mixture of lidocaine and prilocaine (EMLA) cream. METHODS: We conducted this multicentre randomised controlled trial at three tertiary-level children's hospitals in Italy in 2015. Children aged three to 10 years were enrolled in an emergency department, paediatric day hospital and paediatric ward and randomly allocated to receive a warm lidocaine and tetracaine patch or EMLA cream. The primary outcome was the success rate at the first attempt. RESULTS: The analysis included 172 children who received a warm lidocaine and tetracaine patch and 167 who received an EMLA cream. The needle procedure was successful at the first attempt in 158 children (92.4%) who received the warm patch and in 142 children (85.0%) who received the cream (p = 0.03). The pain scores were similar in both groups. CONCLUSION: This study showed that the first-time needle procedure success was 7.4% higher in children receiving a warm lidocaine and tetracaine patch than EMLA cream.
Keywords: Anesthetics, Local; Catheterization, Peripheral; Child; Child, Preschool; Female; Hot Temperature; Humans; Lidocaine; Lidocaine, Prilocaine Drug Combination; Male; Pain; Phlebotomy; Prilocaine; Tetracaine

Fecal Calprotectin: Diagnostic Accuracy of the Immunochromatographic CalFast Assay in a Pediatric Population. - Radillo, Oriano; Pascolo, Lorella; Martelossi, Stefano; Dal Bo, Sara; Ventura, Alessandro (J Clin Lab Anal, 2016)
BACKGROUND: Fecal calprotectin is a noninvasive marker for bowel diseases and it is high valuable to follow disease activity in Crohn's disease (CD) and ulcerative colitis (UC). In this study, we evaluated the diagnostic performance of the recently introduced immunochromatographic assay CalFast in comparison to the well-known ELISA tests for calprotectin assay to obtain a rapid diagnosis of bowel inflammation in pediatric patients. METHODS: CalFast was tested in parallel to the classic ELISA tests CalPrest and PhiCal (gold standards for the calprotectin determination) on 148 fecal samples from pediatric subjects including 104 healthy subjects, 29 with CD, and 15 with UC. RESULTS: In this study, the sensitivity and specificity of CalFast, CalPrest, and PhiCal were 86.4%, 88.6%, and 93.2% and 86.6%, 74%, and 64.4%, respectively. The area under the curve, obtained from receiver operating characteristic analysis, indicated the lack of significant difference among all the kits used. CONCLUSION: The immunochromatographic assay demonstrated good diagnostic predictive values, comparable to those of the ELISA methods, and may represent a valid alternative in order to save operators' time. The test, in fact, has a short turnaround time and does not need a specific ELISA instrumentation.

Frequency of the CCR5-delta32 allele in Brazilian populations: A systematic literature review and meta-analysis. - Silva-Carvalho, Wlisses Henrique Veloso; De Moura, Ronald Rodrigues; Coelho, Antônio Victor Campos; Crovella, Sergio; Guimarães, Rafael Lima (Infect Genet Evol, 2016)
The CCR5 is a chemokine receptor widely expressed by several immune cells that are engaged in inflammatory responses. Some populations have individuals exhibiting a 32bp deletion in the CCR5 gene (CCR5-delta32) that produces a truncated non-functional protein not expressed on the cell surface. This polymorphism, known to be associated with susceptibility to infectious and inflammatory diseases, such as osteomyelitis, pre-eclampsia, systemic lupus erythematous, juvenile idiopathic arthritis, rheumatoid arthritis and HIV/AIDS, is more commonly found in European populations with average frequency of 10%. However, it is also possible to observe a significant frequency in other world populations, such as the Brazilian one. We performed a systematic review and meta-analysis of CCR5-delta32 genetic association studies in Brazilian populations throughout the country to estimate the frequency of this polymorphism. We also compared CCR5-delta32 frequencies across Brazilian regions. The systematic literature reviewed studies involving delta32 allele in Brazilian populations published from 1995 to 2015. Among the reviewed literature, 25 studies including 30 Brazilian populations distributed between the North, Northeast, South and Southeast regions were included in our meta-analysis. We observed an overall allelic frequency of 4% (95%-CI, 0.03-0.05), that was considered moderate and, notably, higher than some European populations, such as Cyprus (2.8%), Italy (3%) and Greece (2.4%). Regarding the regional frequency comparisons between North-Northeast (N-NE) and South-Southeast (S-SE) regions, we observed an allelic frequency of 3% (95%-CI, 0.02-0.04) and 4% (95%-CI, 0.03-0.05), respectively. The populations from S-SE regions had a slightly higher CCR5-delta32 frequency than N-NE regions (OR=1.41, p=0.002). Although there are several studies about the CCR5-delta32 polymorphism and its effect on the immune response of some infectious diseases, this report is the first meta-analysis study that provides a descriptive study of the distribution of CCR5-delta32 allele in Brazilian population.

Failure of interferon-γ pre-treated mesenchymal stem cell treatment in a patient with Crohn's disease. - Taddio, Andrea; Tommasini, Alberto; Valencic, Erica; Biagi, Ettore; Decorti, Giuliana; De Iudicibus, Sara; Cuzzoni, Eva; Gaipa, Giuseppe; Badolato, Raffaela; Prandini, Alberto; Biondi, Andrea; Ventura, Alessandro (World J Gastroenterol, 2015)
Mesenchymal stem cells (MSC) are cells of stromal origin which exhibit unlimited self-renewal capacity and pluripotency in vitro. It has recently been observed that MSC may also exert a profound immunosuppressive and anti-inflammatory effect both in vitro and in vivo with consequent potential use in autoimmune disorders. We present the case of a patient suffering from childhood-onset, multidrug resistant and steroid-dependent Crohn's disease who underwent systemic infusions of MSC, which led to a temporary reduction in CCR4, CCR7 and CXCR4 expression by T-cells, and a temporary decrease in switched memory B-cells, In addition, following MSC infusion, lower doses of steroids were needed to inhibit proliferation of the patient's peripheral blood mononuclear cells. Despite these changes, no significant clinical benefit was observed, and the patient required rescue therapy with infliximab and subsequent autologous hematopoietic stem cell transplantation. The results of biological and in vitro observations after MSC use and the clinical effects of infusion are discussed, and a brief description is provided of previous data on MSC-based therapy in autoimmune disorders.

Fainting Starting Parenteral Nutrition. - Pederiva, Federica; Barbi, Egidio; Zennaro, Floriana; Neri, Elena (Pediatr Emerg Care, 2015)
Complications such as mechanical accidents, infections, and thrombosis are commonly described in the presence of a central venous catheter. We present a case of a boy who had fainting episodes due to dislocation of a central venous catheter.

Fever tree revisited: From malaria to autoinflammatory diseases. - Pastore, Serena; Vuch, Josef; Bianco, Anna Monica; Taddio, Andrea; Tommasini, Alberto (World J Clin Pediatr, 2015)
Over the centuries the idea of recurrent fevers has mainly been associated with malaria, but many other fevers, such as typhoid and diphtheria were cause for concern. It is only in recent times, with the more severe forms of fever from infectious origin becoming less frequent or a cause for worry that we started noticing recurrent fevers without any clear infectious cause, being described as having a pathogenesis of autoinflammatory nature. The use of molecular examinations in many cases can allow a diagnosis where the cause is monogenic. In other cases, however the pathogenesis is likely to be multifactorial and the diagnostic-therapeutic approach is strictly clinical. The old fever tree paradigm developed to describe fevers caused by malaria has been revisited here to describe today's periodic fevers from the periodic fever adenitis pharyngitis aphthae syndrome to the more rare autoinflammatory diseases. This model may allow us to place cases that are yet to be identified which are likely to be of multifactorial origin.

Ficolin Gene Polymorphisms in Systemic Lupus Erythematosus and Rheumatoid Arthritis. - Addobbati, Catarina; De Azevêdo Silva, Jaqueline; A C Tavares, Nathália; Monticielo, Odirlei; M Xavier, Ricardo; T Brenol, João Carlos; Crovella, Sergio; B Chies, José Artur; Sandrin-Garcia, Paula (Ann Hum Genet, 2015)
Systemic lupus erythemathosus (SLE) and rheumatoid arthritis (RA) are complex autoimmune diseases characterized by an immune balance breakdown and by chronic inflammation. Several findings link SLE and RA development with the complement system and ficolin components have emerged as candidates for disease development. Since genetic association studies with ficolin genes in SLE and RA have not yet been conducted in a Brazilian population, the aim of this study was to determine whether polymorphisms of ficolin-1(FCN1) and ficolin-2 (FCN2) genes are associated with SLE and RA susceptibility as well as disease manifestation. Two SNPs within FCN1 (rs2989727 and 1071583) and three in FCN2 (rs17514136, rs3124954, and rs7851696) were studied in 208 SLE and184 RA patients as well as 264 healthy individuals in a Southeast Brazilian population. For SLE patients, the FCN2 rs17514136 SNP was associated with a more severe disease (SLICC) (p = 0.0067). Furthermore, an association between the occurrence of nephritis and the T/T genotype for FCN2 rs3124954 SNP (p = 0.047, OR = 3.17, 95%CI = 1.34-7.5) was observed. No association was observed between the studied polymorphisms and RA development. Thus, our data support involvement of the FCN2 gene in the SLE phenotype.

Food protein-induced enterocolitis syndrome caused by fish and/or shellfish in Italy. - Miceli Sopo, Stefano; Monaco, Serena; Badina, Laura; Barni, Simona; Longo, Giorgio; Novembre, Elio; Viola, Serena; Monti, Giovanna (Pediatr Allergy Immunol, 2015)
BACKGROUND: The study describes the demographic features, culprit foods, clinical features and outcomes for children presenting with acute fish and/or shellfish food protein-induced enterocolitis syndrome (FPIES) in four Italian paediatric allergy centres. METHODS: A retrospective/prospective study was undertaken. All children diagnosed with fish or shellfish FPIES were enrolled. The diagnosis of FPIES was based on Sicherer's or Miceli Sopo clinical criteria. Skin prick tests (SPT) were performed in all patients, at the time of diagnosis and prior to OFC. RESULTS: Seventy children were enrolled. Mean age at first episode was 14 months (range 6-46 months); mean age at diagnosis was 34 months (range 6-164 months). Sole and cod were the fish most commonly implicated. Fifty-seven of 70 (81%) children had FPIES exclusively to fish, 37 of 57 (65%) children had single-fish FPIES, 20 of 57 (35%) multiple-fish FPIES, nine of 70 (13%) presented adverse reactions exclusively to shellfish, and four of 70 (6%) presented adverse reactions to both fish and shellfish. Only four (5.7%) children presented episodes of acute FPIES with different foods (2 to cow's milk, 1 to egg, 1 to beef); in all cases, onset was prior to that of fish or shellfish FPIES. Fifteen of 70 (21%) children tolerated fish other than the offending fish. Twenty-four of 70 (34%) children achieved tolerance (age range 24-102 months). CONCLUSIONS: The chief peculiarities of acute fish and shellfish FPIES, compared to more frequent cow's milk or soy FPIES, are (i) later age of onset, (ii) longer persistence and (iii) possibility of tolerating fish other than the offending fish. Adverse reactions with shellfish are possible.

Functionalized synchrotron in-line phase-contrast computed tomography: a novel approach for simultaneous quantification of structural alterations and localization of barium-labelled alveolar macrophages within mouse lung samples. - Dullin, Christian; dal Monego, Simeone; Larsson, Emanuel; Mohammadi, Sara; Krenkel, Martin; Garrovo, Chiara; Biffi, Stefania; Lorenzon, Andrea; Markus, Andrea; Napp, Joanna; Salditt, Tim; Accardo, Agostino; et al. (J Synchrotron Radiat, 2015)
Functionalized computed tomography (CT) in combination with labelled cells is virtually non-existent due to the limited sensitivity of X-ray-absorption-based imaging, but would be highly desirable to realise cell tracking studies in entire organisms. In this study we applied in-line free propagation X-ray phase-contrast CT (XPCT) in an allergic asthma mouse model to assess structural changes as well as the biodistribution of barium-labelled macrophages in lung tissue. Alveolar macrophages that were barium-sulfate-loaded and fluorescent-labelled were instilled intratracheally into asthmatic and control mice. Mice were sacrificed after 24 h, lungs were kept in situ, inflated with air and scanned utilizing XPCT at the SYRMEP beamline (Elettra Synchrotron Light Source, Italy). Single-distance phase retrieval was used to generate data sets with ten times greater contrast-to-noise ratio than absorption-based CT (in our setup), thus allowing to depict and quantify structural hallmarks of asthmatic lungs such as reduced air volume, obstruction of airways and increased soft-tissue content. Furthermore, we found a higher concentration as well as a specific accumulation of the barium-labelled macrophages in asthmatic lung tissue. It is believe that XPCT will be beneficial in preclinical asthma research for both the assessment of therapeutic response as well as the analysis of the role of the recruitment of macrophages to inflammatory sites.
Keywords: Algorithms; Allergens; Animals; Asthma; Barium Sulfate; Cell Line, Transformed; Cell Movement; Contrast Media; Disease Models, Animal; Female; Image Processing, Computer-Assisted; Imaging, Three-Dimensional; Lung; Macrophages, Alveolar; Mice; Mice, Inbred BALB C; Microscopy, Fluorescence; Ovalbumin; Synchrotrons; Tomography, X-Ray Computed

F402L variant in NLRP12 in subjects with undiagnosed periodic fevers and in healthy controls. - De Pieri, Carlo; Vuch, Josef; Athanasakis, Emmanouil; Severini, Giovanni Maria; Crovella, Sergio; Bianco, Anna Monica; Tommasini, Alberto (Clin Exp Rheumatol, 2014)
Keywords: Cryopyrin-Associated Periodic Syndromes; Female; Humans; Intracellular Signaling Peptides and Proteins; Male; Mutation

Fate of lymphocytes after withdrawal of tofacitinib treatment. - Piscianz, Elisa; Valencic, Erica; Cuzzoni, Eva; De Iudicibus, Sara; De Lorenzo, Elisa; Decorti, Giuliana; Tommasini, Alberto (PLoS One, 2014)
Tofacitinib (Tofa) is an inhibitor of Janus Kinase 3, developed for the treatment of autoimmune diseases and for the prevention of transplant rejection. Due to its selective action on proliferating cells, Tofa can offer a way to block T cell activation, without toxic effects on resting cells. However, few studies have investigated the effects of Tofa on lymphocyte activation in vitro. Our aim was to study the action of Tofa on different lymphocyte subsets after in vitro stimulation and to track the behaviour of treated cells after interruption of the treatment. Peripheral blood lymphocytes were stimulated in vitro with mitogen and treated with two concentrations of Tofa. After a first period in culture, cells were washed and further incubated for an additional time. Lymphocyte subsets, activation phenotype and proliferation were assessed at the different time frames. As expected, Tofa was able to reduce the activation and proliferation of lymphocytes in the first four days of treatment. In addition the drug led to a relative decrease of Natural Killer, B cells and CD8 T cells compared to CD4 T cells. However, treated cells were still viable after the first period in culture and begun to proliferate, strikingly, in a dose dependent manner when the drug was removed from the environment by replacing the culture medium. This novel data does not necessarily predict a similar behaviour in vivo, but can warn about the clinical use of this drug when a discontinuation of treatment with Tofa is considered for any reason.
Keywords: Antigens, CD; B-Lymphocytes; CD4-Positive T-Lymphocytes; CD8-Positive T-Lymphocytes; Cell Proliferation; Drug Administration Schedule; Humans; Janus Kinase 3; Killer Cells, Natural; Lymphocyte Activation; Lymphocyte Count; Phytohemagglutinins; Piperidines; Primary Cell Culture; Protein Kinase Inhibitors; Pyrimidines; Pyrroles

The first trimester gravid serum regulates procalcitonin expression in human macrophages skewing their phenotype in vitro. - Rami, Damiano; La Bianca, Martina; Agostinis, Chiara; Zauli, Giorgio; Radillo, Oriano; Bulla, Roberta (Mediators Inflamm, 2014)
Procalcitonin (PCT) is one of the best diagnostic and prognostic markers in clinical practice, widely used to evaluate the evolution of bacterial infections. Although it is mainly produced by thyroid, during sepsis almost all the peripheral tissues are involved in PCT production. Parenchymal cells have been suggested as the main source of PCT expression; however the contribution of macrophages is not clear yet. In response to environmental cues, tissue macrophages acquire distinct functional phenotypes, ranging from proinflammatory (M1) to anti-inflammatory (M2) phenotype. Macrophages at the fetal-maternal interface show immunosuppressive M2-like activities required for the maintenance of immunological homeostasis during pregnancy. This study aims to clarify the ability to synthesise PCT of fully differentiated (M0), polarized (M1/M2) macrophages and those cultured either in the presence of first trimester gravid serum (GS) or pregnancy hormones. We found out that M1 macrophages upregulate PCT expression following LPS stimulation compared to M0 and M2. The GS downregulates PCT expression in macrophages, skewing them towards an M2-like phenotype. This effect seems only partially mediated by the hormonal milieu. Our findings strengthen the key role of macrophages in counteracting inflammatory stimuli during pregnancy, suggesting PCT as a possible new marker of M1-like macrophages.
Keywords: Biomarkers; Calcitonin; Cells, Cultured; Chorionic Gonadotropin; Estradiol; Female; Gene Expression Regulation; Homeostasis; Humans; Inflammation; Macrophages; Monocytes; Phenotype; Pregnancy; Pregnancy Trimester, First; Protein Precursors; Serum; Up-Regulation

From tube to breast: the bridging role of semi-demand breastfeeding. - Davanzo, Riccardo; Strajn, Tamara; Kennedy, Jacqueline; Crocetta, Anna; De Cunto, Angela (J Hum Lact, 2014)
Determination of the optimal timing of breastfeeding initiation for preterm infants is still a challenge for health professionals. Often unjustified delays and restrictions of breastfeeding occur due to non-evidence-based current opinions about preterm infants' feeding capacity. Semi-demand feeding has been proposed for preterm infants during the transition from scheduled to full demand feeding, to promote the establishment of self-regulated oral feeding. Although semi-demand feeding has been shown to be safe and effective in reducing time to reaching oral feeding, the implementation of this feeding pattern for preterm infants in the neonatal intensive care unit (NICU) is still limited. We developed a protocol for the application of semi-demand feeding in preterm infants based on the existing knowledge of preterm infant neurodevelopment and NICU organization and staff experience. The protocol's aim is to attain successful transition from tube feeding to breastfeeding. In this article, we describe the protocol used in the neonatal unit of the Maternal and Child Health Institute of Trieste, a third level care center in northeastern Italy.

Family history in early-onset inflammatory bowel disease. - Bianco, Anna Monica; Zanin, Valentina; Monasta, Lorenzo; Martelossi, Stefano; Marcuzzi, Annalisa; Crovella, Sergio (J Gastroenterol, 2013)
Keywords: Colitis, Ulcerative; Crohn Disease; Female; Humans; Male

Febrile urinary tract infections in young children: recommendations for the diagnosis, treatment and follow-up. - Ammenti, Anita; Cataldi, Luigi; Chimenz, Roberto; Fanos, Vassilios; La Manna, Angela; Marra, Giuseppina; Materassi, Marco; Pecile, Paolo; Pennesi, Marco; Pisanello, Lorena; Sica, Felice; Toffolo, Antonella; et al. (Acta Paediatr, 2012)
UNLABELLED: We report the recommendations for the diagnosis, treatment, imaging evaluation and use of antibiotic prophylaxis in children with the first febrile urinary tract infection, aged 2 months to 3 years. They were prepared by a working group of the Italian Society of Pediatric Nephrology after careful review of the available literature and a consensus decision, when clear evidence was not available. CONCLUSION: These recommendations are endorsed by the Italian Society of Pediatric Nephrology. They can also be a tool of comparison with other existing guidelines in issues in which much controversy still exists.
Keywords: Anti-Bacterial Agents; Child, Preschool; Female; Fever; Follow-Up Studies; Humans; Infant; Male; Urinary Tract Infections

First trimester maternal serum PIGF, free β-hCG, PAPP-A, PP-13, uterine artery Doppler and maternal history for the prediction of preeclampsia. - Di Lorenzo, G; Ceccarello, M; Cecotti, V; Ronfani, L; Monasta, L; Vecchi Brumatti, L; Montico, M; D'Ottavio, G (Placenta, 2012)
OBJECTIVE: To evaluate the detection of pregnancy hypertensive disorders by integrating maternal history, serum biomarkers and uterine artery Doppler in the first trimester. METHODS: We prospectively recruited 2118 women that underwent an 11-13 weeks aneuploidy screening. We gathered information on maternal history, uterine artery Doppler and serum biomarkers (PAPP-A, PlGF, PP-13 and free β-hCG). Models were developed for the prediction of overall preeclampsia (PE), early-onset PE, late-onset PE and gestational hypertension (GH). For each outcome, we performed a multivariate logistic regression starting from the saturated model: adopting a step-down procedure we excluded all factors not statistically significant (p > 0.05). Sensitivity models only for statistically significant parameters were calculated from the ROC curves for fixed false-positive rates (FPR). RESULTS: Among 2118 women, 46 (2.17%) developed GH and 25 (1.18%) were diagnosed with PE, including 12 (0.57%) early-onset PE and 13 (0.61%) late-onset PE. For a fixed FPR of 10 and 5%, serum PlGF, free β-hCG and chronic hypertension identified respectively 67 and 75% of women who developed early-onset PE. In the model for the prediction of overall PE the combination of the uterine artery Doppler pulsatility index (UtA PI) with PlGF and chronic hypertension reached a sensitivity of 60% for a 20% of FPR. CONCLUSION: An integration of maternal characteristics and first trimester maternal serum biomarkers (free β-hCG and PlGF) provided a possible screening for early-onset PE. In the overall PE model, UtA PI turned out to be statistically significant but did not improve the detection rate.
Keywords: Adult; Biological Markers; Chorionic Gonadotropin, beta Subunit, Human; Cohort Studies; Female; Galectins; Humans; Hypertension, Pregnancy-Induced; Pre-Eclampsia; Pregnancy; Pregnancy Complications; Pregnancy Proteins; Pregnancy Trimester, First; Pregnancy-Associated Plasma Protein-A; Prospective Studies; Ultrasonography, Prenatal; Uterine Artery; Uterus

Formation of membrane-defined compartments by tick-borne encephalitis virus contributes to the early delay in interferon signaling. - Miorin, Lisa; Albornoz, Amelina; Baba, Marycelin M; D'Agaro, Pierlanfranco; Marcello, Alessandro (Virus Res, 2012)
Interferons are key mediators of the innate antiviral response of the cell against viral infections. Viruses on the other hand have evolved various strategies to delay innate immunity in order to establish a productive infection. In this work we analyzed the pathway of interferon induction by the tick-borne encephalitis virus. We initially observed a consistent delay of interferon induction following virus replication. RIG-I, but not MDA5, and nuclear translocation of IRF3 were eventually required for interferon activation pointing to a defect in pattern recognition receptor's signaling. However, viral proteins could not directly inhibit the pathway suggesting an indirect mechanism. We found that dsRNA replication intermediates and replicated viral RNA localized to membrane-defined perinuclear compartments that resisted RNAse treatment. Thus, initial escape from innate immunity involved the formation of replication vesicles that may function as a barrier to pattern recognition receptors.
Keywords: Cell Membrane; Encephalitis Viruses, Tick-Borne; Humans; Immune Evasion; Interferons; Receptors, Pattern Recognition; RNA, Viral; Signal Transduction

Frequency of human papillomavirus types 16, 18, 31, and 33 and sites of cervical lesions in gynecological patients from Recife, Brazil. - Baldez da Silva, M F P T; Guimarães, V; Silva, M A R; Medeiros do Amaral, C M; Beçak, W; Stocco, R C; Freitas, A C; Crovella, S (Genet Mol Res, 2012)
Human papilloma virus (HPV) is a well-established cause of cervical cancer. While many studies have been performed so far on HPV viral biology, mode of infection and prevention measures, scanty information is available on lesion sites of infected women and the incidence of viral types at specific locations. We looked for a possible relationship between the most common viral types (HPVs 16, 18, 31, 33) found in Recife, PE, Brazil, and lesion sites. We examined 396 HPV-positive women at the Gynecological Unit of the IMIP at Recife; 288 women were positive for HPV 16, 18, 31, or 33, present as a single-virus type or as co-infection. HPV 16 was the most frequent virus type found in the vulva, vagina, uterine cervix-vagina, and uterine cervix. HPV 31 was the second prevalent virus type in vulva, vagina, uterine cervix-vagina, uterine cervix, and mole. HPVs 18 and 33 were present with similar frequencies in the mole-vulva region. Among the co-infections, HPV 16/18 and HPV16/31 were the most frequent in our study group, followed by HPV 16/33.
Keywords: Adolescent; Adult; Brazil; Cervix Uteri; DNA, Viral; Female; Human papillomavirus 16; Human papillomavirus 18; Human papillomavirus 31; Humans; Papillomavirus Infections; Uterine Cervical Diseases; Young Adult

From bone marrow transplantation to cellular therapies: possible therapeutic strategies in managing autoimmune disorders. - Taddio, Andrea; Biondi, Andrea; Piscianz, Elisa; Valencic, Erica; Biagi, Ettore; Badolato, Raffaele (Curr Pharm Des, 2012)
Chronic inflammatory disorders occurring in childhood represent a serious therapeutic challenge. However, available therapies seem not to be targeted on the pathogenic mechanism of the disease and are often not actively affecting the natural history of the disease. Emerging treatments might be of some benefit to many patients who did not respond to conventional therapeutic options. Biological therapies with monoclonal antibodies and other recombinant proteins have been introduced in clinical practice. At the same time, mesenchymal stromal cells (MSC) have gained attention as a savage treatment in patients subjected to hematopoietic stem cell transplantation who develop severe graft versus host disease (GvHD); in addition, recent reports from clinical trials on larger cohorts of patients support their use as second-line treatment after failure of corticosteroid treatment. For analogy, they have been proposed for the treatment of intractable autoimmune disorders. Hematopoietic stem cell transplantation (HSCT) has been shown to be effective for treatment of rheumatic disorder cases that were resistant to traditional therapies especially if combined with cell manipulation techniques, such as selection of regulatory T cell and depletion of harmful lymphocytes. We herein present the rationale of different strategies, the preliminary data obtained in clinical trials, unsolved problems and possible next developments of novel treatment protocols of autoimmune disorders.
Keywords: Autoimmune Diseases; Bone Marrow Transplantation; Child; Chronic Disease; Graft vs Host Disease; Hematopoietic Stem Cell Transplantation; Humans; Inflammation; Lymphocytes; Mesenchymal Stem Cell Transplantation; T-Lymphocytes, Regulatory; Treatment Outcome

Functional single-nucleotide polymorphisms in the DEFB1 gene are associated with systemic lupus erythematosus in Southern Brazilians. - Sandrin-Garcia, P; Brandão, L A C; Guimarães, R L; Pancoto, J A T; Donadi, E A; Lima-Filho, J L de; Segat, L; Crovella, S (Lupus, 2012)
Systemic lupus erythematosus (SLE) is an autoimmune disease that results in inflammation and tissue damage. The etiology of SLE remains unknown, but recent studies have shown that the innate immune system may have a role in SLE pathogenesis through the secretion of small cationic peptides named defensins. The aim of the study was to determine the possible involvement in SLE of three functional single nucleotide polymorphisms (SNPs) (c.-52G>A, c.-44C>G and c.-20G>A) in the 5'UTR region of DEFB1 gene, by analyzing them in a population of 139 SLE patients and 288 healthy controls. The c.-52G>A SNP showed significant differences in allele and genotype frequency distribution between SLE patients and controls (p = 0.01 and p = 0.02 respectively) indicating protection against SLE (A allele, OR = 0.68, AA genotype OR = 0.51). Significant differences were also observed for c.-44C>G SNP, the C/G genotype being associated with susceptibility to SLE (OR = 1.60, p = 0.04). Moreover, statistically significant differences between patients and controls were found for two DEFB1 haplotypes (GCA and GGG, p = 0.01 and p = 0.02 respectively). When considering DEFB1 SNPs and SLE clinical and laboratory manifestations, significant association was found with neuropsychiatric disorders, immunological alterations and anti-DNA antibodies. In conclusion, our results evidence a possible role for the c.-52G>A and c.-44C>G DEFB1 polymorphisms in SLE pathogenesis, that can be considered as possible risk factors for development of disease and disease-related clinical manifestations. Additional studies are needed, to corroborate these results as well as functional studies to understand the biological role of these SNPs in the pathogenesis of SLE.
Keywords: Adolescent; Adult; Aged; beta-Defensins; Brazil; Case-Control Studies; Female; Genetic Predisposition to Disease; Genotype; Haplotypes; Humans; Lupus Erythematosus, Systemic; Male; Middle Aged; Polymorphism, Single Nucleotide; Risk Factors; Young Adult

The farnesyltransferase inhibitors tipifarnib and lonafarnib inhibit cytokines secretion in a cellular model of mevalonate kinase deficiency. - Marcuzzi, Annalisa; De Leo, Luigina; Decorti, Giuliana; Crovella, Sergio; Tommasini, Alberto; Pontillo, Alessandra (Pediatr Res, 2011)
The shortage of geranylgeranyl-pyrophosphate (GGPP) was associated to an increased IL-1β release in the autoinflammatory syndrome mevalonate kinase deficiency (MKD), a rare inherited disease that has no specific therapy. Farnesyltransferase inhibitors (FTIs) act at the end of mevalonate pathway. Two FTIs, tipifarnib (Tip) and lonafarnib (Lon), were therefore evaluated as possible therapeutical choices for the treatment of MKD. FTIs could lead to a redirection of the limited available number of mevalonate intermediates preferentially to GGPP synthesis, eventually preventing the uncontrolled inflammatory response. The effect of Tip and Lon on intracellular cholesterol level (ICL) and on proinflammatory cytokines secretion was evaluated in a cellular model of MKD, chemically obtained treating RAW 264.7 cells with lovastatin (Lova) and alendronate (Ald). The combination of FTIs with the isoprenoid geraniol (GOH) was also tested both in this model and in monocytes isolated from MKD patients. Tip and Lon proved to revert the ICL lowering and to significantly reduce the lipopolysaccharide-induced cytokines secretion in Ald-Lova -RAW 264.7 cells. This anti-inflammatory effect was amplified combining the use of GOH with FTIs. The effect of GOH and Tip was successfully replicated in MKD patients' monocytes. Tip and Lon showed a dramatic anti-inflammatory effect in monocytes where mevalonate pathway was chemically or genetically impaired.
Keywords: Alendronate; Animals; Anti-Inflammatory Agents; Cell Line; Child; Child, Preschool; Cholesterol; Cytokines; Dose-Response Relationship, Drug; Enzyme Inhibitors; Farnesyltranstransferase; Humans; Inflammation Mediators; Lovastatin; Male; Mevalonate Kinase Deficiency; Mice; Monocytes; Phosphotransferases (Alcohol Group Acceptor); Piperidines; Polyenes; Polyisoprenyl Phosphates; Polyunsaturated Alkamides; Pyridines; Quinolones; Terpenes

Fine tuning of protein kinase C (PKC) isoforms in cancer: shortening the distance from the laboratory to the bedside. - Bosco, R; Melloni, E; Celeghini, C; Rimondi, E; Vaccarezza, M; Zauli, G (Mini Rev Med Chem, 2011)
The serine/threonine protein kinase C (PKC) family was first identified as intracellular receptor(s) for the tumor promoting agents phorbol esters. Thirty years after the discovery of PKC, the role of specific PKC isoforms has been described in relationship with an altered pattern of expression in different types of cancer and a good number of small molecule inhibitors (inhibitory peptides, antisense oligonucleotides or natural compounds) targeting PKC are now available. Despite all these achievements and a huge amount of basic research studies on the biochemical regulation of PKC, there has been a delay in clinical trials with drugs targeting PKC function. This delay is easily explained taking into account the extreme biological complexity of the PKC family of isoforms and the incomplete understanding of the specific role of each PKC isozyme in different types of cancers. Some of the difficulties in developing pharmacological compounds selectively tuning the different PKCs have started to be overcome. In this review, the growing evidences of the role of the PKC isoforms α, βII, δ, ε, ζ and ι is in promoting or counteracting tumor progression will be discussed in relationship with promising therapeutic perspectives.
Keywords: Antineoplastic Agents; Biological Products; Enzyme Inhibitors; Humans; Isoenzymes; Neoplasms; Oligonucleotides, Antisense; Peptides; Protein Kinase C

Foreign children with cancer in Italy. - Rondelli, Roberto; Dini, Giorgio; De Rosa, Marisa; Quarello, Paola; Bisogno, Gianni; Aricò, Maurizio; Vasconcelos, Carivaldo; Tamaro, Paolo; Casazza, Gabriella; Zecca, Marco; De Laurentis, Clementina; Porta, Fulvio; et al. (Ital J Pediatr, 2011)
BACKGROUND: There has been a noticeable annual increase in the number of children coming to Italy for medical treatment, just like it has happened in the rest of the European Union. In Italy, the assistance to children suffering from cancer is assured by the current network of 54 centres members of the Italian Association of Paediatric Haematology and Oncology (AIEOP), which has kept records of all demographic and clinical data in the database of Mod.1.01 Registry since 1989. METHODS: We used the information stored in the already mentioned database to assess the impact of immigration of foreign children with cancer on centres' activity, with the scope of drawing a map of the assistance to these cases. RESULTS: Out of 14,738 cases recorded by all centres in the period from 1999 to 2008, 92.2% were born and resident in Italy, 4.1% (608) were born abroad and living abroad and 3.7% (538) were born abroad and living in Italy. Foreign children cases have increased over the years from 2.5% in 1999 to. 8.1% in 2008.Most immigrant children came from Europe (65.7%), whereas patients who came from America, Asia and Oceania amounted to 13.2%, 10.1%, 0.2%, respectively. The immigrant survival rate was lower compared to that of children who were born in Italy. This is especially true for acute lymphoblastic leukaemia patients entered an AIEOP protocol, who showed a 10-years survival rate of 71.0% vs. 80.7% (p < 0.001) for immigrants and patients born in Italy, respectively. CONCLUSIONS: Children and adolescents are an increasingly important part of the immigration phenomenon, which occurs in many parts of the world. In Italy the vast majority of children affected by malignancies are treated in AIEOP centres. Since immigrant children are predominantly treated in northern Italy, these centres have developed a special expertise in treating immigrant patients, which is certainly very useful for the entire AIEOP network.
Keywords: Adolescent; Africa; Asia; Child; Child, Preschool; Databases, Factual; Emigrants and Immigrants; Ethnic Groups; Europe, Eastern; European Union; Female; Humans; Incidence; Infant; Infant, Newborn; Italy; Male; Neoplasms; North America; Oceania; Prevalence; Retrospective Studies; South America; Survival Rate

Forkhead box protein 3 (FOXP3) mutations lead to increased TH17 cell numbers and regulatory T-cell instability. - Passerini, Laura; Olek, Sven; Di Nunzio, Sara; Barzaghi, Federica; Hambleton, Sophie; Abinun, Mario; Tommasini, Alberto; Vignola, Silvia; Cipolli, Marco; Amendola, Mario; Naldini, Luigi; Guidi, Luisa; et al. (J Allergy Clin Immunol, 2011)
Keywords: Forkhead Transcription Factors; Gene Expression Regulation; Genetic Diseases, X-Linked; Humans; Immunologic Deficiency Syndromes; Intestinal Diseases; Male; Mutation; Polyendocrinopathies, Autoimmune

Frequency distribution of HLA DQ2 and DQ8 in celiac patients and first-degree relatives in Recife, northeastern Brazil. - Castro-Antunes, Margarida Maria; Crovella, Sergio; Brandão, Lucas André Cavalcanti; Guimarães, Rafael Lima; Motta, Maria Eugênia Farias Almeida; Silva, Giselia Alves Pontes da (Clinics (Sao Paulo), 2011)
AIMS: The aim of this study was to evaluate the frequencies of the HLA genotypes DQ2 and DQ8 and the alleles A1*05, A1*0201, B1*0201 and B1*0302 in individuals with celiac disease in Recife, northeastern Brazil. METHODS: HLA DQ2 and DQ8 genotyping was performed for 73 individuals with celiac disease and 126 first-degree relatives with negative transglutaminase serology. The alleles DQA1*05, DQA1*0201, DQB1*02 and DQB1*0302 were identified by sequencing using specific primers and the EU-DQ kit from the Eurospital Laboratory, Trieste, Italy and double-checked by the All Set SPP kit (Dynal). RESULTS: Among the 73 cases, 50 (68.5%) had the genotype DQ2, 13 (17.8%) had DQ8, 5 (6.8%) had DQ2 and DQ8, and 5 did not have any of these genotypes. Among the 5 negative individuals, four had the B1*02 allele and one did not have any of the alleles studied. B1*02 was the most frequent allele in both groups (94% in the patients and 89% in the control relatives). CONCLUSIONS: In this study, celiac disease was associated with the genotypes DQ2 and DQ8. DQ2 predominated, but the distribution of the frequencies was different from what has been found in European populations and was closer to what has been found in the Americas. The high frequencies of the HLA genotypes DQ2 and DQ8 that were found in first-degree relatives would make it difficult to use these HLA genotypes for routine diagnosis of celiac disease in this group.
Keywords: Adolescent; Adult; Brazil; Celiac Disease; Chi-Square Distribution; Child; Child, Preschool; Cross-Sectional Studies; Europe; Family; Female; Gene Frequency; Genetic Predisposition to Disease; HLA-DQ Antigens; Humans; Infant; Male; Middle Aged; Young Adult

Frequency of HLA B*5701 allele carriers in abacavir treated-HIV infected patients and controls from northeastern Brazil. - Crovella, Sergio; Biller, Lara; Santos, Sergio; Salustiano, Ana; Brandão, Lucas; Guimarães, Rafael; Segat, Ludovica; Lima Filho, Jose Luiz de; Arraes, Luiz Claudio (Clinics (Sao Paulo), 2011)
Keywords: Adolescent; Adult; Anti-HIV Agents; Brazil; Case-Control Studies; Dideoxynucleosides; Drug Hypersensitivity; Female; Gene Frequency; Genotype; HIV Infections; HLA-B Antigens; Humans; Male; Middle Aged; Real-Time Polymerase Chain Reaction; Young Adult

Functional type 1 regulatory T cells develop regardless of FOXP3 mutations in patients with IPEX syndrome. - Passerini, Laura; Di Nunzio, Sara; Gregori, Silvia; Gambineri, Eleonora; Cecconi, Massimiliano; Seidel, Markus G; Cazzola, Giantonio; Perroni, Lucia; Tommasini, Alberto; Vignola, Silvia; Guidi, Luisa; Roncarolo, Maria G; et al. (Eur J Immunol, 2011)
Mutations of forkhead box p3 (FOXP3), the master gene for naturally occurring regulatory T cells (nTregs), are responsible for the impaired function of nTregs, resulting in an autoimmune disease known as the immune dysregulation, polyendocrinopathy, enteropathy, X-linked (IPEX) syndrome. The relevance of other peripheral tolerance mechanisms, such as the presence and function of type 1 regulatory T (Tr1) cells, the major adaptive IL-10-producing Treg subset, in patients with IPEX syndrome remains to be clarified. FOXP3(mutated) Tr1-polarized cells, differentiated in vitro from CD4(+) T cells of four IPEX patients, were enriched in IL-10(+) IL-4(-) IFN-γ(+) T cells, a cytokine production profile specific for Tr1 cells, and expressed low levels of FOXP3 and high levels of Granzyme-B. IPEX Tr1 cells were hypoproliferative and suppressive, thus indicating that FOXP3 mutations did not impair their function. Furthermore, we isolated Tr1 cell clones from the peripheral blood of one FOXP3(null) patient, demonstrating that Tr1 cells are present in vivo and they can be expanded in vitro in the absence of WT FOXP3. Overall, our results (i) show that functional Tr1 cells differentiate independently of FOXP3, (ii) confirm that human Tr1 and nTregs are distinct T-cell lineages, and (iii) suggest that under favorable conditions Tr1 cells could exert regulatory functions in IPEX patients.
Keywords: Cell Differentiation; Cell Lineage; Cells, Cultured; Enteritis; Forkhead Transcription Factors; Genetic Diseases, X-Linked; Humans; Immunity, Innate; Interleukin-2 Receptor alpha Subunit; Mutation; Polyendocrinopathies, Autoimmune; Syndrome; T-Lymphocytes, Regulatory

Fasting increases tobramycin oral absorption in mice. - De Leo, Luigina; Di Toro, Nicola; Decorti, Giuliana; Malusà, Noelia; Ventura, Alessandro; Not, Tarcisio (Antimicrob Agents Chemother, 2010)
The pharmacokinetics of the aminoglycoside tobramycin was evaluated after oral administration to fed or fasting (15 h) mice. As expected, under normal feeding conditions, oral absorption was negligible; however, fasting induced a dramatic increase in tobramycin bioavailability. The dual-sugar test with lactulose and l-rhamnose confirmed increased small bowel permeability via the paracellular route in fasting animals. When experiments aimed at increasing the oral bioavailability of hydrophilic compounds are performed, timing of fasting should be extremely accurate.
Keywords: Administration, Oral; Animals; Anti-Bacterial Agents; Biological Availability; Fasting; Injections, Intramuscular; Injections, Intravenous; Intestinal Absorption; Lactulose; Male; Mice; Mice, Inbred BALB C; Rhamnose; Tobramycin

First case in Italy of acquired resistance to oseltamivir in an immunocompromised patient with influenza A/H1N1v infection. - Campanini, Giulia; Piralla, Antonio; Rovida, Francesca; Puzelli, Simona; Facchini, Marzia; Locatelli, Franco; Minoli, Lorenzo; Percivalle, Elena; Donatelli, Isabella; Baldanti, Fausto (J Clin Virol, 2010)
A pandemic influenza A/H1N1v strain with the neuraminidase H274Y mutation was detected in nasal secretions of a 2-year-old leukemic patient with influenza-like illness after 18 days of treatment with oseltamivir. At baseline, no drug-resistant virus was found, while 4 days after treatment initiation a mixture of wild-type and mutated virus was detected. After treatment interruption, the wild type influenza virus re-emerged and became prevalent in nasal secretions after a few days, suggesting the lower fitness of the mutated virus strain. The patient slowly improved concurrently with a decrease in virus load, which resulted negative 42 days after diagnosis. No other drug-resistant influenza A/H1N1v virus strains have been detected in Italy (up to the end of November 2009) since the first case of the novel A/H1N1v virus was identified in the country (May 2009).
Keywords: Amino Acid Substitution; Antiviral Agents; Bodily Secretions; Child, Preschool; Drug Resistance, Viral; Female; Humans; Immunocompromised Host; Influenza A Virus, H1N1 Subtype; Influenza, Human; Italy; Molecular Sequence Data; Mutation, Missense; Neuraminidase; Nose; Oseltamivir; RNA, Viral; Sequence Analysis, DNA; Treatment Outcome; Viral Load; Viral Proteins; Withholding Treatment

Five new OTOF gene mutations and auditory neuropathy. - Zadro, Cristina; Ciorba, Andrea; Fabris, Annalisa; Morgutti, Marcello; Trevisi, Patrizia; Gasparini, Paolo; Martini, Alessandro (Int J Pediatr Otorhinolaryngol, 2010)
OBJECTIVE: Purpose of this paper is to analyse OTOF gene in a series of subjects affected by auditory neuropathy. METHODS: Four children showing mild to profound prelingual deafness, confirmed by the absence of a clear and detectable responses at auditory brainstem responses (ABR), associated with the presence of bilateral OAE, were enrolled in the study. RESULTS AND CONCLUSIONS: Genetic analysis identified five new mutations (a nonsense, a small and a large deletion and two splicing site mutations), and one missense mutation (F1795C) previously described. These results further confirm the role of OTOF gene in auditory neuropathy. In the absence of a context of neurological syndrome, the combination of absent ABR and positive OAE responses should lead to an auditory neuropathy diagnosis and to a mutational screening in OTOF.
Keywords: Auditory Diseases, Central; Deafness; Evoked Potentials, Auditory, Brain Stem; Female; Humans; Male; Membrane Proteins; Mutation; Otoacoustic Emissions, Spontaneous; Polymerase Chain Reaction

Follow-up and quality of life of patients with cryopyrin-associated periodic syndromes treated with Anakinra. - Lepore, Loredana; Paloni, Giulia; Caorsi, Roberta; Alessio, Maria; Rigante, Donato; Ruperto, Nicola; Cattalini, Marco; Tommasini, Alberto; Zulian, Francesco; Ventura, Alessando; Martini, Alberto; Gattorno, Marco (J Pediatr, 2010)
OBJECTIVE: To evaluate the quality of life and long-term follow-up of patients enrolled in the Italian registry of cryopyrin-associated periodic syndromes (CAPS). STUDY DESIGN: Since 2004, 20 patients with CAPS were enrolled in a common registry from different Italian Centers of Pediatric Rheumatology; 14 patients were treated with Anakinra in an open fashion. Both treated and untreated patients were routinely followed according to standard of care. The Child Health Questionnaire (CHQ-PF 50) was used to assess the health-related quality of life. RESULTS: The mean duration of follow-up was 37.5 months. In all treated patients, a complete and persistent control of the inflammatory manifestations was observed with no further progression of the disease. At enrollment in the registry, patients showed a poorer health-related quality of life than healthy children in both physical and the psychosocial summary scores. Treatment was associated with a dramatic and sustained amelioration of a variety of measures of poor quality of life, particularly in those concerning the global health perception, bodily pain-discomfort, and other physical domains. CONCLUSIONS: Long-term IL-1 blockade produces a significant and persistent improvement in the clinical manifestations associated with the disease and on the overall quality of life.
Keywords: Adolescent; Adult; Case-Control Studies; Child; Child, Preschool; Cryopyrin-Associated Periodic Syndromes; Female; Follow-Up Studies; Humans; Inflammation; Interleukin 1 Receptor Antagonist Protein; Interleukin-1; Male; Phenotype; Quality of Health Care; Quality of Life; Questionnaires; Syndrome; Treatment Outcome

Formate assay in body fluids: application in methanol poisoning. - Makar, A B; McMartin, K E; Palese, M; Tephly, T R (Biochem Med, 1975)
Keywords: Aldehyde Oxidoreductases; Animals; Body Fluids; Carbon Dioxide; Formates; Haplorhini; Humans; Hydrogen-Ion Concentration; Kinetics; Methanol; Methods; Pseudomonas